Ιnnovative Health Promotion Strategies: A 6-Month Longitudinal Study on Computerized Cognitive Training for Older Adults with Minor Neurocognitive Disorders - Anna Tsiakiri; Spyridon Plakias; Pinelopi Vlotinou; Paraskevi Athanasouli; Aikaterini Terzoudi; Sotiria Kyriazidou; Aspasia Serdari; Georgia Karakitsiou; Kalliopi Megari; Nikolaos Aggelousis; Konstantinos Vadikolias; Foteini Christidi (European Journal of Investigation in Health, Psychology and Education)
Minor neurocognitive disorders (NCDs) represent a transitional phase between normal cognitive aging and dementia, highlighting the importance of early interventions. This study assessed the efficacy of a structured 6-month computerized cognitive training (CCT) program in stabilizing cognitive decline among older adults with minor NCDs. One hundred participants were randomly assigned to an intervention group or a non-intervention group. The intervention group underwent weekly, personalized CCT sessions using the MeMo program, which targeted memory, attention, and adaptability. Cognitive performance was measured at baseline and after six months using the Cambridge Cognitive Examination (CAMCOG). Statistical analysis showed significant cognitive decline in the non-intervention group in orientation (p = 0.032), language expression (p = 0.008), praxis (p = 0.008), and memory (p = 0.01). In contrast, the intervention group showed no significant changes, except for a minor decline in perception (p = 0.003). These results suggest that CCT may help delay cognitive deterioration in minor NCDs. However, while cognitive decline was stabilized, no significant improvement was observed. Further research is recommended to investigate the long-term benefits and the transferability of cognitive gains. The findings support the use of CCT as a non-pharmacological health promotion strategy for enhancing cognitive resilience in aging populations. The novelty of this research lies in its focus on adaptive CCT as a non-pharmacological intervention, highlighting the potential role of neuroplasticity in delaying cognitive decline and offering new insights into personalized cognitive health strategies for aging populations.